2008
DOI: 10.1097/ta.0b013e318065c02a
|View full text |Cite
|
Sign up to set email alerts
|

Does HIV Infection Influence Outcomes After Trauma?

Abstract: Although HIV-infected patients suffer more complications than their noninfected counterparts, HIV does not alter the outcomes for trauma patient. HIV status should not influence management decisions for these patients regardless of the patient's CD4 count.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 12 publications
2
13
0
1
Order By: Relevance
“…However, it seems that the degree of contamination of the wound in open injuries (Guth et al 1996, Harrison et al 2002) and the lifestyle of the patients (Habermann et al 2008) have more influence on outcome than HIV infection alone. There is increasing evidence both from high-income countries and from LMICs that the end outcomes after surgery in general are no worse for patients with HIV than for other patients (Cacala et al 2006, Duane et al 2008, Stock et al 2010, Patel et al 2011). …”
Section: Discussionmentioning
confidence: 99%
“…However, it seems that the degree of contamination of the wound in open injuries (Guth et al 1996, Harrison et al 2002) and the lifestyle of the patients (Habermann et al 2008) have more influence on outcome than HIV infection alone. There is increasing evidence both from high-income countries and from LMICs that the end outcomes after surgery in general are no worse for patients with HIV than for other patients (Cacala et al 2006, Duane et al 2008, Stock et al 2010, Patel et al 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Duane et al conducted a retrospective study comparing outcomes of HIV positive and HIV negative patients over a 5-year period in the trauma unit. They found no difference in infection rates or overall complications based on CD4 + count alone (Duane et al, 2008). Conversely, Karpelowsky et al showed that in children who were HIV positive or exposed to HIV had increased rates of poor wound healing and breakdown of reconstruction sites (Karpelowsky et al, 2009).…”
Section: Management and Outcome Of Hiv Positive Patients In Traumamentioning
confidence: 99%
“…To date, the effects of HIV on trauma has been mixed in the literature. Martin et al showed increased 30-day mortality in trauma patients [4] while other studies demonstrated no association with mortality [6][7][8][9][10]. Similarly, some studies have shown higher renal and pulmonary complications [5,6] as well as higher infectious complications [5,7,8],…”
Section: Introductionmentioning
confidence: 99%